2019
DOI: 10.1002/cpt.1644
|View full text |Cite
|
Sign up to set email alerts
|

Use of Insulin and the Risk of Progression of Pancreatitis: A Population‐Based Cohort Study

Abstract: Acute pancreatitis (AP) often progresses to recurrent acute pancreatitis (RAP) and chronic pancreatitis (CP). We investigated the relationship between the use of insulin after AP and progression from AP to RAP or CP, as well as the effect of diabetes status on the relationship. Using nationwide pharmaceutical dispensing data and hospital discharge data, insulin‐naïve individuals were followed from first AP admission. Multivariable time‐dependent Cox regression analyses were conducted. In the overall cohort (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The present study adds to the existing literature on factors that characterize NODAP. Several studies have demonstrated that there are differences between NODAP and T2DM in the gut hormone response [8], blood glucose control [9], risk of pancreatic cancer [10], risk of mortality [11], and survival benefit following the use of common antidiabetic medications [12,13]. To date, only one study has linked IPFD to insulin sensitivity in individuals with NODAP [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study adds to the existing literature on factors that characterize NODAP. Several studies have demonstrated that there are differences between NODAP and T2DM in the gut hormone response [8], blood glucose control [9], risk of pancreatic cancer [10], risk of mortality [11], and survival benefit following the use of common antidiabetic medications [12,13]. To date, only one study has linked IPFD to insulin sensitivity in individuals with NODAP [26].…”
Section: Discussionmentioning
confidence: 99%
“…There are also several lines of epidemiological evidence that showed that outcomes of NODAP and T2DM are different. These include the risks of poor glycemic control [9], pancreatic cancer [10], mortality [11], and the risk-benefit ratio of common antidiabetic medications [12,13]. Hence, a thorough understanding of the mechanisms behind impaired glucose metabolism in patients after AP is critical with a view to improving clinical management and identifying potential novel targets for prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, all individuals included in the study were non-athletic and did not report any sudden weight gain or weight loss. Fourth, given that CP itself is a risk factor for the development of pancreatic cancer and taken into account that it is already known that periostin is elevated in pancreatic cancer, there is a possibility that the elevated plasma levels of periostin in the CP group (compared with the AP and healthy control groups) might have been related to pancreatic cancer that was masked as CP [ 38 , 48 , 49 ]. However, all participants underwent MRI and pancreatic cancer was excluded a priori.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with PPDM also have a significantly higher risk of mortality and hospitalization compared with T2DM individuals [ 5 ]. Further, the effectiveness of common glucose-lowering medications is different in PPDM compared with T2DM [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%